Ideal Cardiovascular Health, Cardiovascular Remodeling, and Heart Failure in Blacks: The Jackson Heart Study. (February 2017) - Spahillari, Aferdita; Talegawkar, Sameera; Correa, Adolfo; Carr, J. Jeffrey; Terry, James G.; Lima, João; Freedman, Jane E.; Das, Saumya; Kociol, Robb; de Ferranti, Sarah; Mohebali, Donya; Mwasongwe, Stanford; et al.
Abstract : Background—: The lifetime risk of heart failure (HF) is higher in the black population than in other racial groups in the United States. Methods and Results—: We measured the Life's Simple 7 ideal cardiovascular health metrics in 4195 blacks in the JHS (Jackson Heart Study; 2000–2004). We evaluated the association of Simple 7 metrics with incident HF and left ventricular structure and function by cardiac magnetic resonance (n=1188). Mean age at baseline was 54.4 years (65% women). Relative to 0 to 2 Simple 7 factors, blacks with 3 factors had 47% lower incident HF risk (hazard ratio [HR], 0.53; 95% confidence interval [CI], 0.39–0.73; P <0.0001); and those with ≥4 factors had 61% lower HF risk (HR, 0.39; 95% CI, 0.24–0.64; P =0.0002). Higher blood pressure (HR, 2.32; 95% CI, 1.28–4.20; P =0.005), physical inactivity (HR, 1.65; 95% CI, 1.07–2.55; P =0.02), smoking (HR, 2.04; 95% CI, 1.43–2.91; P <0.0001), and impaired glucose control (HR, 1.76; 95% CI, 1.34–2.29; P <0.0001) were associated with incident HF. The age-/sex-adjusted population attributable risk for these Simple 7 metrics combined was 37.1%. Achievement of ideal blood pressure, ideal body mass index, ideal glucose control, and nonsmoking was associated with less likelihood of adverse cardiac remodeling by cardiac magnetic resonance. Conclusions—: Cardiovascular risk factors in midlife (specifically elevated blood pressure, physical inactivity, smoking, and poor glucose control) are associated with incident HF in blacks and represent targets for intensified HF prevention. Abstract : Supplemental Digital Content is available in the text.